The Need for ICT in Adult Education for Socio-Economic Development in Maiduguri, Borno State, Nigeria - Itodo, Andrew; Oluwasesan, Ojo (Machakos University, 2018)
The thrust of the study was to examine the need of ICT in Adult Education for socio-economic development in Maiduguri, Borno state. In this light, the study adopted questionnaire method for data collection, simple frequency distribution and percentage rate were used to analyse the collected data from schools. The study investigated the level of introduction of ICT in Adult education and its benefits to individuals and societies for socio-economic development. The study revealed that the use and introduction of ICT in adult education is less but it was ascertained that ICT contributes a lot in human endeavors. The study suggested that there is need for adult educators and special education specialists to collaborate to develop ICT literacy primers, e-learning and distance education programmes, assistive technology and therapy services for adults within the community. This will enable learning take place in the life of these individuals, ICT integration to adult education should be emphasised, fully recognized and have affordable physical structures, facilities and resource materials readily available to most adult education centres in Maiduguri, the adults should be sensitized on the need of adult education for socio-economic development and not just to promote their salary scheme in their place of work as this study revealed and finally, there is need for an uninterrupted electricity / power supply situation in Nigeria so that there will be opportunities for significant improvements and increase in ICT awareness among the rural and urban dwellers. Keywords: ICT, Adult, Education, Socio-Economic, Development, Maiduguri
Keywords: ICT